2005
DOI: 10.1021/jf051380g
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Bile Acid Binding of Flours from Oat Lines Varying in Percentage and Molecular Weight Distribution of β-Glucan

Abstract: Two experimental high beta-glucan oat (Avena sativa) lines (7.64 and 8.05%) and two traditional lines (4.77 and 5.26% beta-glucan) were used to evaluate the effect of beta-glucan quantity and molecular weight on bile acid (BA) binding. The oat flour samples were digested by an in vitro system that simulated human digestion. No significant differences among oat type were found in the overall beta-glucan, starch, and pentosan digestibilities. Considering the standard, cholestyramine, as 100% bound, the relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(81 citation statements)
references
References 25 publications
6
72
2
1
Order By: Relevance
“…The authors concluded that other components of the oat fraction might also have contributed to the bile acid binding. This is supported by the study of Sayar et al [38] which described that partial lichenase hydrolysis did not affect bile acid binding of β-glucan-rich oat fractions using an in vitro centrifugation method. These results support our hypothesis that centrifugation-based methods do not reflect the impact of viscosity on the reabsorption of bile acids.…”
Section: Discussionsupporting
confidence: 66%
“…The authors concluded that other components of the oat fraction might also have contributed to the bile acid binding. This is supported by the study of Sayar et al [38] which described that partial lichenase hydrolysis did not affect bile acid binding of β-glucan-rich oat fractions using an in vitro centrifugation method. These results support our hypothesis that centrifugation-based methods do not reflect the impact of viscosity on the reabsorption of bile acids.…”
Section: Discussionsupporting
confidence: 66%
“…The low MW and medium MW β-glucan bound more bile acid than did the high MW β-glucan. The bile-acid binding values of the oat flours from different oat lines and oat bran were in the range of 6% to13.5% (4,19).…”
Section: Resultsmentioning
confidence: 99%
“…The human digestive process of inulin was simulated in vitro by using the method described in Sayar et al, 2005 [31]. Inulin Frutafit IQ solution (150 mg/mL) was subjected to a cooking step in boiling water for 4 minutes.…”
Section: Methodsmentioning
confidence: 99%